OMIC-13. THE ROLE OF COPY NUMBER ALTERATIONS IN PREDICTING SURVIVAL AND INFLUENCING TREATMENT OF CHILDHOOD BRAIN TUMORS. (1st June 2021) - Freshour, Sharon; Fisk, Bryan; Miller, Christopher; Griffith, Obi; Griffith, Malachi; Rubin, Joshua
Abstract: Brain and central nervous system tumors are the most common form of solid tumor cancers and the second most common cancer overall among children. While many advances have been made in understanding the genomics of childhood brain tumors in recent years, the role of copy number alterations (CNAs) has not been fully characterized. Although the genomes of childhood brain tumor patients are generally considered to be relatively stable diploid genomes, analysis of a subset of pretreatment diagnostic samples from a cohort of 84 deceased patients from Washington University revealed widespread alterations, suggesting CNAs may play a larger role in the progression and prognosis of childhood brain tumors than originally thought. Follow up analysis of the entire cohort, containing a variety of tumor types that had low-pass whole genome sequencing performed, similarly showed evidence of CNAs across samples. 75 out 84 patients showed the presence of CNAs with an average of 16% of the genome being altered per sample and a median of 7%. Preliminary results examining correlations between the percentage of the genome that was copy number altered and event free survival or overall survival indicated that CNA percentage may have some prognostic value. For example, ependymoma samples showed positive correlation between alteration percentage and overall survival, while glioblastoma samples showed negative correlation. To explore copy number alteration in a larger cohort and increase statistical power, similar analyses are being performed using an additional 950 samples from the Pediatric Brain Tumor Atlas curated by The Children's Brain Tumor Network (CBTN) to determine if CNVs and CNV percentage or specific alterations can serve as prognostic markers and whether the biology of this genomic instability could inform therapeutic strategy.